Engaging businesses and faith-based organizations in public health interventions: Lessons learned from a COVID-19 and flu vaccine detailing program in the Northeast Bronx - Fatoumata Diallo; Lissette Paulino; Lauren J. Shiman; Kim Freeman; Brandon Brooks; Diana Banson; Anita Reyes (Elsevier, 2023)
Objectives: The NYC Department of Health and Mental Hygiene conducted a COVID-19 and flu vaccine community detailing program to influential businesses and faith-based organizations in the Northeast Bronx in 2022 to increase COVID-19 and flu vaccine knowledge and uptake among residents of the area. Study design: program evaluation. Methods: The program was piloted in the Northeast Bronx, a geography selected based on prior low COVID-19 and flu vaccination rates and high COVID-19 case positivity rates. Barbershops, hair salons, beauty salons, nail salons and faith-based organizations were selected as potential partners because their owners or staff typically spend at least an hour in interactions with clients. From January 2022 through April 2022, two detailing visits were conducted by engagement staff: an initial visit to all potential partners in the selected geography, and a follow up visit to those who committed to be champions of health. Results: Out of 113 identified businesses/organizations, 70 met the criteria to be potential partners in the program. After being contacted by health department staff, 45 (64%) potential partners committed to be champions of health. During the four months of the pilot, zip codes with the highest level of program engagement experienced greater percent increases in COVID-19 vaccination rates during the program period compared to NYC and Bronx averages. Flu vaccination rates during the program period were not available. Conclusion: Supplementing other local public health efforts, the community detailing pilot program demonstrates a model of dissemination of health information through local business leaders, and provides lessons learned to increase champion commitment.